SOCIALIZATION OF PERSONALITY IN THE CONTEXT OF COMPETENCE APPROACH - Sergeeva; Bondarenko; Shebzuhova; Vartumyan; Slepenok; Getmanova (Revista Inclusiones, 2019)
Introduction. In the context of the transition of modern Russia to civil society and civilized market, special emphasis in the process of modernization of education is placed on training graduates to function as full members of society and citizens of their country. Research methodology. Modern understanding of competence includes both the ability and skill to perform certain functions, and the presence of a number of mental qualities that allow acting independently and responsibly. Research results. The phenomenon of competence has a certain hierarchy, revealed on the grounds of scale, content and methods of formation. Ensuring the growth of competence is inextricably linked with the personal values system. Therefore, the identification of value orientations of the individual, helping him to understand them better, the resolution of value conflicts and evaluation of alternatives are the basis of any program in this direction. Discussion. Social competence of the person assumes that he, first of all: carries himself to members of society; owns the moral and ethical standards peculiar to society; realizes need of orientation of all activity for the benefit of society; assumes social responsibility for consequences of the acts; cooperates with other members of society; is capable to flexible change of a social role; is ready to changes and is capable to influence process of changes in the interpersonal relations; seeks and is able to cause in society interest to his professional and public activity; aspires to compliance of the professional and public status to individual and personal qualities. Conclusion. Personality is considered as a complex dynamic structural formation. The phenomenon of self-development can be identified as the main internal mechanism of personality development. The importance of personal self-development is determined by its regulatory function.